Nghiên cứu chính sách đưa giáo dục AI vào giáo dục phổ thông của một số nước và đề xuất cho Việt Nam - Bùi, Diệu Quỳnh; Hồ, Thị Thu Hương (Tạp chí Giáo dục, 2025)
A comprehensive review of approaches to artificial intelligence (AI) education in K-12 systems across selected countries such as the United States, China, Canada, Germany, and Singapore allows us to learn from effective models, stay updated with global trends, and develop policies tailored to our national context. This, in turn, enhances education quality and prepares a digital-ready workforce for the future. The study reveals that while some countries choose to introduce AI as a standalone subject, many others integrate AI content into existing subjects such as Mathematics, Science, Technology, and Computing. AI education content not only covers technical knowledge but also addresses ethical, social, and critical thinking aspects related to AI. These findings suggest that AI education in Vietnam should be implemented promptly, based on the realities of the national education system. The process should begin with developing a national AI literacy competency framework for K-12 education, followed by integrating AI content into subjects, and establishing networks that connect schools with technology experts to ensure effective implementation.